Creative Writing Process among Pre-service EFL Teachers in the Indonesian Context: A Translanguaging Approach - Riyantika, Fajar; Prasetya, Rian Andri; Puteri, Celiacika Gustisiwi (FKIP Universitas Lampung, 2024)
Abstract: Creative Writing Process among Pre-service EFL Teachers in the Indonesian Context: A translanguaging approach. Translanguaging has been common practice in EFL environment, especially in the process of teaching and learning. This paper aims to investigate pre-service teachers’ translanguaging practices and attitudes toward the pedagogical approach in EFL Creative Writing Class. This study is conducted through a qualitative design with three steps of data collection; giving creative writing project, classroom observation, and interview. The sample in this study is pre-service English teachers of Lampung University. The data analysis are done by highlighting the translanguaging practice among students during the process of short-story production. The analyzed data show that translanguaging occurs in every phase of the writing process. The participants of this study applied translanguaging not only to develop their short-story, but also to give feedback to their classmates’ works. The study’s implications, limitations, and recommendations for future research are also discussed to provide clearer path on possible development of studies in the field of translanguaging. Keywords: Creative writing, perceptions towards translanguaging, short story, translanguaging, translanguaging pedagogical approachDOI: http://dx.doi.org/10.23960/jpp.v14.i1.202404